2014
DOI: 10.3233/ves-140536
|View full text |Cite
|
Sign up to set email alerts
|

CANVAS an update: Clinical presentation, investigation and management

Abstract: BACKGROUND: Cerebellar Ataxia with Neuropathy and bilateral Vestibular Areflexia Syndrome (CANVAS) is a multi-system ataxia which results in cerebellar ataxia, a bilateral vestibulopathy and a somatosensory deficit. This sensory deficit has recently been shown to be a neuronopathy, with marked dorsal root ganglia neuronal loss. The characteristic oculomotor clinical sign is an abnormal visually enhanced vestibulo-ocular reflex. OBJECTIVE: To outline the expanding understanding of the pathology in this conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 41 publications
1
105
0
4
Order By: Relevance
“…The pathophysiology of CANVAS is not completely understood; however, this condition is reported as a ganglionopathy involving the sensory, vestibular, autonomic, facial, and trigeminal ganglia. 3,4 Previous pathological studies in CANVAS have demonstrated atrophy of the vestibular, facial, and trigeminal nerves and of the dorsal root ganglia. 1,4,11 The nonlengthdependent nature of sensory loss observed on neurophysiological testing in our cases supports a sensory ganglionopathy/neuronopathy rather than a classic length-dependent axonal sensory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiology of CANVAS is not completely understood; however, this condition is reported as a ganglionopathy involving the sensory, vestibular, autonomic, facial, and trigeminal ganglia. 3,4 Previous pathological studies in CANVAS have demonstrated atrophy of the vestibular, facial, and trigeminal nerves and of the dorsal root ganglia. 1,4,11 The nonlengthdependent nature of sensory loss observed on neurophysiological testing in our cases supports a sensory ganglionopathy/neuronopathy rather than a classic length-dependent axonal sensory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Previous pathological studies in CANVAS have demonstrated atrophy of the vestibular, facial, and trigeminal nerves and of the dorsal root ganglia. 1,4,11 The nonlengthdependent nature of sensory loss observed on neurophysiological testing in our cases supports a sensory ganglionopathy/neuronopathy rather than a classic length-dependent axonal sensory neuropathy. This is consistent with neurophysiological testing results in 14 CANVAS patients who were diagnosed with a sensory neuronopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Romberg test on foam rubber has a sensitivity of up to 79% and a specificity of up to 80% for detecting both patients with unilateral and those with bilateral vestibular loss (Petersen et al, 2013, Fujimoto et al, 2009b. Although abnormalities in the other vestibular tests during physical examination can be found (Kheradmand & Zee 2012;Szmulewicz et al, 2014), this review will not focus on them, since the main challenges for diagnosing and quantifying BVH are not encountered in these tests, except for HIT and the test for DVA; they will be discussed separately below.…”
Section: Neuro-otological and Vestibular Physical Examinationmentioning
confidence: 99%
“…magnetic resonance imaging, computed tomography), lumbar puncture, sensory nerve action potentials, speech assessment, etc. (Zingler et al, 2008a(Zingler et al, , 2009Jen 2009;Szmulewicz et al, 2011Szmulewicz et al, , 2014Requena et al, 2014). However, these tests are mainly used for determination of coexisting problems or the etiology of BVH (Table 2.1), not for an evaluation of vestibular function.…”
Section: Other Diagnostic Testsmentioning
confidence: 99%